Game changers : the unsung heroines of sports history - Schiot, Molly (Simon and Schuster, 2016)
"Based on the Instagram account @TheUnsungHeroines, a celebration of the pioneering, forgotten female athletes of the twentieth century that features rarely seen photos and new interviews with past and present gamechangers including Abby Wambach and Cari Champion"--